Analisis Komparatif UI/UX Aplikasi Pemesanan Transportasi Online Menggunakan System Usability Scale (SUS) dan Heuristik Evaluation - Paisal; Dian Nugraha; Bakhtiar .K; Mariana Purba; Dwi Fitri Brianna; Lemi Iryani; Nia Umilizah; Aulia Aryani; Rizki Adi Saputra; Eldhiyano Pratama; Novita Nurjannah Putri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze and compare the User Interface (UI) and User Experience (UX) of three online transportation applications in Palembang City, namely Gojek, Grab, and Maxim. The rapid growth of Indonesia’s online transportation industry, which reached 88.3 million users in 2024, highlights the importance of evaluating usability quality. Palembang has unique geographical characteristics, as the city is divided by the Musi River, creating specific challenges for app-based transportation services. The novelty of this study lies in the integration of the System Usability Scale (SUS) with Nielsen’s heuristic evaluation within an urban geographical context fragmented by natural barriers. A descriptive comparative approach was employed, involving 120 active users and three UI/UX expert evaluators. The results show that Gojek achieved the highest SUS score of 78.5 (Good), followed by Grab with 75.2 (Good) and Maxim with 68.7 (OK). One-Way ANOVA indicates significant differences among the applications (F = 12.847; p < 0.001). Theoretically, these findings demonstrate that an integrated usability evaluation approach provides a more comprehensive understanding of UI/UX quality in geographically specific contexts.